Flow boiling heat transfer of R245fa under hypergravity realized by rotating machine. (5th November 2022) - Luo, Zufen; Fang, Xiande; Qin, Yeqi; Li, Chong; Li, Xiaohuan
Highlights: Hypergravity obtained through rotation is different from that without rotation. Coriolis force is supposed to involve in enhancing flow boiling heat transfer. Hypergravity might affect flow pattern for low mass flux and heat flux conditions. Increasing heat flux or mass flux could diminish the gravitational effect. Abstract: To measure the influence of hypergravity on flow boiling heat transfer, an experiment with refrigerant R245fa flowing inside a horizontal 1.62 mm tube was conducted, and a turntable was used to simulate the hypergravity environment. Four experimental conditions consisted of the combinations of two mass fluxes (351, 705 kg/m 2 s) and two heat fluxes (32, 64 kW/m 2 ) were tested under nominal gravity levels from 1 g to 2.77 g and a pressure of 217.8 kPa. The heat transfer enhancement was observed in both sing-phase flow and two-phase flow when the turntable started to turn, which reveals the particularity of the hypergravity environment realized by rotating machine and the contributions of the Coriolis force due to rotation. As the hypergravity increased further, the heat transfer phenomena were different for different vapor qualities when performed in low mass flux and low heat flux conditions. At low vapor qualities, it was hard to judge whether the heat transfer was enhanced or deteriorated, but it was slightly deteriorated at high vapor qualities before dry-out and enhanced in the region of post dry-out. In addition, the gravitational effect diminished when increasing heat flux or mass flux, while the heat transfer enhancement caused by the tube rotation did not diminish. Besides, the data analysis was also performed to confirm the source of the heat transfer enhancement when the turntable started to turn.